Factors Affecting Corporate Income Tax Payable: Solvability, Debt To Equity Ratio, and Profit Management - Hollysaa, Pristine; Kuntadi, Cris (Universitas Wiralodra, 2023)
Previous or relevant research is fundamental in a study or scientific article. Previous or relevant research strengthens the theory and phenomenon of the relationship or influence between variables. This article reviews the factors influencing corporate income tax payable, namely Solvability, Debt to Equity Ratio, and Earnings Management, a literature study on tax accounting. This article aims to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Solvability affects corporate income tax payable; 2) Debt to Equity Ratio affects the Income Tax Payable; and 3) Profit Management has a significant effect on Corporate Income Tax Payable